CONCEPTS OF GUARDIANSHIP AND SPONSORSHIP: ADOPTION - Mamatova Mavluda Toirovna (Journals Park Publishing, 2024)
The intricate process of adoption, often hailed as a beacon of hope for both prospective parents and children in need, transcends the mere transfer of legal rights and responsibilities. It weaves together a complex tapestry of legal, social, and emotional considerations, where concepts of guardianship and sponsorship take center stage. This article explores these intertwined notions, illuminating the diverse facets of adoption and their profound implications for all involved
Keywords: childcare, legal issues, laws, protection acts, government endeavor, responsibility.